Clinical and radiological predictors of recanalisation and outcome of 40 patients with acute basilar artery occlusion treated with intra-arterial thrombolysis. Issue 6 (14th May 2004) - Arnold, M; Nedeltchev, K; Schroth, G; Baumgartner, R W; Remonda, L; Loher, T J; Stepper, F; Sturzenegger, M; Schuknecht, B; Mattle, H P
Abstract : Objective: To define predictors of recanalisation and clinical outcome of patients with acute basilar artery occlusions treated with local intra-arterial thrombolysis (IAT). Methods: Vascular risk factors, severity of the neurological deficit graded by the National Institutes of Health stroke scale (NIHSS), and radiological findings were recorded at presentation. Outcome was measured using the modified Rankin scale (mRS) three months later and categorised as favourable (mRS 0–2), poor (mRS 3–5), or death (mRS 6). Results: 40 patients were studied. Median NIHSS on admission was 18. Mean time from symptom onset to treatment was 5.5 hours (range 2.3 to 11). Outcome was favourable in 14 patients (35%) and poor in nine (23%); 17 (42%) died. There were two symptomatic cerebral haemorrhages (5%). Recanalisation of the basilar artery was achieved in 32 patients (80%); it was complete (TIMI grade 3) in 20% and partial (TIMI grade 2) in 60%. In multivariate logistic regression analysis, low NIHSS score on admission (p = 0.002) and vessel recanalisation (p = 0.005) were independent predictors of favourable outcome. Recanalisation occurred more often with treatment within six hours of symptom onset (p = 0.003) and when admission computed tomography showed a hyperdense basilar artery sign (p = 0.007). In a univariate model, quadriplegia (p = 0.002) and coma (p = 0.004) were associated with a poor outcome or death. Conclusions: Low baseline NIHSS on admission and recanalisation of basilar artery occlusions predict a favourable outcome after intra-arterial thrombolysis. Early initiation of IAT and the presence of a hyperdense basilar artery sign on CT were associated with a higher likelihood of recanalisation.